2022
DOI: 10.1161/circulationaha.121.057978
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Gain-of-Function LIPC Variant as a Novel Cause of Familial Combined Hypocholesterolemia

Abstract: Background: Atherosclerotic cardiovascular disease is the main cause of mortality worldwide and is strongly influenced by circulating low-density lipoprotein (LDL) cholesterol levels. Only a few genes causally related to plasma LDL cholesterol levels have been identified so far, and only 1 gene, ANGPTL3 , has been causally related to combined hypocholesterolemia. Here, our aim was to elucidate the genetic origin of an unexplained combined hypocholesterolem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…Detailed variant-driven structure-function assessment of other key players in the lipase pathways (eg, apolipo- proteins, chaperones, inhibitors) will add to our understanding of the biology of these proteins and enhance our therapeutic arsenal. These interesting findings by Dijk et al 6 arose from the discovery of a private variant identified in a single family with an extreme lipid phenotype. Careful mechanistic study of this variant revealed LIPC-E97G as the first GoF variant in HL and demonstrates the power of "N of 1" discoveries in humans with extreme phenotypes.…”
Section: Article See P 724mentioning
confidence: 98%
See 2 more Smart Citations
“…Detailed variant-driven structure-function assessment of other key players in the lipase pathways (eg, apolipo- proteins, chaperones, inhibitors) will add to our understanding of the biology of these proteins and enhance our therapeutic arsenal. These interesting findings by Dijk et al 6 arose from the discovery of a private variant identified in a single family with an extreme lipid phenotype. Careful mechanistic study of this variant revealed LIPC-E97G as the first GoF variant in HL and demonstrates the power of "N of 1" discoveries in humans with extreme phenotypes.…”
Section: Article See P 724mentioning
confidence: 98%
“…These interesting findings by Dijk et al 6 arose from the discovery of a private variant identified in a single family with an extreme lipid phenotype. Careful mechanistic study of this variant revealed LIPC -E97G as the first GoF variant in HL and demonstrates the power of “N of 1” discoveries in humans with extreme phenotypes.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…LIPC not only remodels LDL and HDL but also enhances lipid and lipoprotein uptake [ 37 ]. Interestingly, LIPC gene mutation is the second most common cause of familial hypocholesterolemia, after only angiopoietin-like 3 (ANGPTL3) [ 38 ], suggesting that LIPC is a promising target for the diagnosis of familial hypocholesterolemia.…”
Section: The Clinical Value Of Mir-26 Quantificationmentioning
confidence: 99%
“…A number of rare genetic variants cause low levels of low-density lipoprotein cholesterol (LDL-C) and are associated with a reduced risk of atherosclerotic cardiovascular disease (ASCVD). Recently, a novel gain-of-function genetic variant in hepatic lipase (called LIPC-E97G ) was identified in a family with combined hypocholesterolemia (low LDL-C, low high-density lipoprotein cholesterol, normal triglyceride and apolipoprotein B concentrations) 4. The index case developed ASCVD at age 61 despite having low LDL-C levels (40 mg/dL or 1 mmol/L); other affected family members did not have ASCVD.…”
Section: Cardiovascular Medicine — Lipid Disordersmentioning
confidence: 99%